Internalization of Prophetic Values in Improving Academic and Non-Academic Achievement of Vocational School Students Manbaul Ulum Tangsil Vonosari Bondowoso - Manna Wassalwa, Siti Masyarafatul (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research describes and explains the internalization of prophetic values in improving the academic and non-academic achievements of students at Manbaul Ulum Tangsil Vonosari Bondowoso Vocational School. By using a descriptive qualitative approach with phenomenological analysis, naturalistic research methods, because the research was carried out in natural conditions (natural setting). Data collection used interview techniques, observation and document analysis. Data analysis techniques used Miles and Hubberman analysis, namely data collection, data display, data reduction and data verification. And researchers can collect all the data needed to choose according to the research topic and can present it in the form of a detailed description. To obtain the validity of the data, data triangulation and source and method triangulation are used. The research results of this research are the concepts applied in the internalization of prophetic values in improving the academic and non-academic achievements of students at Manbaul Ulum Tangsil Bondowoso Vocational School which prioritizes the ways and processes in which students adopt, apply and make prophetic values an integral part. from the knowledge, behavior and attitudes of students who prioritize morals, humanist ethics and manners, liberation and transcendence which are taught in Islamic boarding schools with Islamic nuances, faith, Ihsan and being human beings, become a benchmark for the personality of Manbaul Ulum Vocational School students as an integral institution in Islamic boarding schools. Manbaul Ulum, the way to measure academic achievement at Manbaul Ulum Vocational School is through exams, assignments and grades, while non-academic achievement assessments can involve performance-based evaluations, presentations or competition results. The internalization of prophetic values has important value in personal formation and overall development of students, and can provide an overview of students' potential, interests and talents in accordance with academic and non-academic achievements determined by the school.